Three PV plants performance analysis using the principal component analysis method. (15th September 2020) - Adar, Mustapha; Najih, Youssef; Gouskir, Mohamed; Chebak, Ahmed; Mabrouki, Mustapha; Bennouna, Amin
Abstract: This paper presents a comparative analysis of the performance of three grid-connected photovoltaic power plants, of about 2kWp for each plant, using the principal component analysis (PCA) method. These systems include three silicon technologies. The analysis is based on the performance parameters described in the international standard IEC 61724. To perform this comparative analysis, the energy production, the operational and the meteorological data are first collected for a period of time. The performance evaluation of PV plants is then performed based on several performance indicators such as Final Yield, Performance Ratio, System Losses, Capture Losses, Array Efficiency and Capacity Factor. Using the PCA method, the correlation between the performance parameters and the meteorological variables is then studied and analyzed. The resulting analysis shows that the Polycrystalline silicon technology is the most performing one. The annual average values of the Performance Ratio were found to be 86.66% for the polycrystalline against 84.76% and 83%, for the monocrystalline and amorphous, respectively. For the daily data, the PCA method reveals that the Performance Ratio is independent of the solar irradiation but it has a slight correlation with temperature and System Losses and a strong correlation with Capture Losses. The result shows also that the temperature acts slightly on the amorphous compared to the crystalline ones. Highlights: Performance of three Silicon Photovoltaics technologies is analyzed. The performance parameters are used to evaluate the proposed system. Principal Component Analysis is carried out using R software. Correlation analysis is conducted using 11 inputs of different variables of each Silicon technology. A dimensionality reduction of the 11 input variables into 2 dimensions is presented.